The Implementation of the Tilawati Method in Learning Qur'an at Madrasah Aliyah - Khoirotul Idawati; Devind Camelia Rossa; Daeng Fuadi A Kadir Tajawok; Hanifudin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
The lack of religious education among students can influence their behavior and negatively impact the quality of their Qur’an recitation. Therefore, this study aims to explore the implementation of the Tilawati method in Qur’an learning for students. The research was conducted at Madrasah Aliyah Al-Asy'ari Keras Diwek, Jombang, using a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The learning process focuses on two primary outcomes: enhancing students' character and improving their Qur’an reading skills. Over time, the madrasa aspires to equip students with essential life skills through Qur’an learning using the Tilawati method, recognizing it as a relevant and effective approach in 21st-century education. The findings reveal that Qur’an instruction using the Tilawati method follows several key stages. It begins with opening activities, such as reciting a prayer before the lesson. This is followed by the core learning activities, which include classical techniques such as the use of teaching aids, and the application of the rost rhythmic style. The session concludes with closing activities involving evaluation and the recitation of kafaratul majlis (closing prayer). The implication of this study underscores the importance of applying appropriate methods for teaching the Qur’an in madrasas to achieve both spiritual and educational development.